Community Food Insecurity and Child Maltreatment Reports: County-Level Analysis of U.S. National Data From 2009 to 2018. Issue 1 (January 2023) - Kim, Hyunil; Gundersen, Craig; Windsor, Liliane
Current literature suggests that food insecurity increases child maltreatment risk. Yet, existing evidence is limited to individual-level associations among low-income, high-risk populations based on local, mostly urban data. This study aims to generalize prior findings to community-level associations in general populations, using national data including all urban-rural areas. We examined, for the first time, if food insecurity rates increase child maltreatment report (CMR) rates at the county level after controlling for potential confounders. We examined both within-community longitudinal changes (i.e., within-effects) and inter-community differences (i.e., between-effects) of food insecurity rates and their associations with CMR rates. We also examined differences by age, sex, race/ethnicity, maltreatment type, and urbanicity. We constructed longitudinal county-level data by linking multiple national databases, including all substantiated and unsubstantiated CMR records, the Map the Meal Gap's community food insecurity estimates, and Census data. The data covered over 96% of U.S. counties from 2009 to 2018. For analysis, we used within-between random effects models. Regarding between-effects, we found that in inter-community comparisons, higher food insecurity rates were significantly associated with increased CMR rates. This association was consistent by age, sex, maltreatment type, and urbanicity. For within-effects, we found that the association between longitudinal changes of food insecurity rates and CMR rates significantly differed by urbanicity. Specifically, longitudinal increases of food insecurity rates significantly increased CMR rates among large urban counties, but not among small urban and rural counties. Study findings highlight the importance of conducting further research to better understand the mechanisms through which food insecurity impact child maltreatment at both individual and community levels. Our community-level findings from general populations especially have significant implications for community-based programs and large-scale policies to achieve population-level impact on child well-being.